(3bhGYO GdRQcTis - (3eMeO Hf HgGOQ Hf YHO Gddg GdRQcTj, CHh YHO Gddg, HOQ GdOjf , J (B794 (3g`s ((3Ydi Hf GdeMSf Hf Ydi Hf YeQ s)
(3ChdgG (B:s
(3CeG HYO aEf VHW GdCehQ GdefJTQI GdeJYOOI ai GdbhGfjf GdeJMOI s
(3BNQgG (B:s
(3hcGf CSJGPg aNQ GdOjf GdQGRi jMaX YTQI GdGa fcJI ai GdLOd s
(3GdfSNI HgG MhGTs
(3JcQQ CjVkG Qbe (B" 74" (3CUhd abgs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1359s
Keywords: (3CUhd Gdabgs